Heterosexual Men and Women Both Show a Hypothalamic Response to the Chemo-Signal Androstadienone - Burke, Sarah M. (Public Library of Science, 2012)
The odorous steroid compound 4,16-androstadien-3-one (androstadienone), found in axillary sweat, was previously reported to evoke hypothalamic activation in heterosexual women, but not in heterosexual men. However, subjects were exposed to the pure crystalline form of androstadienone, which raised the question whether the observed hypothalamic response is physiologically relevant. Therefore, in the present study, we asked whether sexually dimorphic hypothalamic responses could be measured when subjects were exposed to lower, more physiologically relevant concentrations of androstadienone. A total of 21 women and 16 men, all heterosexual, participated in our functional magnetic resonance imaging study (fMRI). Three different concentrations of androstadienone diluted in propylene glycol (10 mM “high,” 0.1 mM “medium” and 0.001 mM “low”) were delivered to the subjects’ nostrils using a computer-controlled stimulator. When exposed to the “high” androstadienone concentration, women showed stronger hypothalamic activation than men. By contrast, men showed more hypothalamic activation when exposed to the “medium” androstadienone concentrations in comparison to women. Thus, we replicated that smelling the chemo-signal androstadienone elicits a hypothalamic activation. However, this effect does not seem to be gender-specific, because androstadienone activated the hypothalamus in both men and women, suggesting that androstadienone exerts specific effects in heterosexual individuals of both sexes.